Pengaruh Motivasi, Sarana Prasarana, dan Lingkungan Belajar Terhadap Prestasi Olahraga Peserta Didik Cabang Olahraga Shorinji Kempo di SMANKo Flobamorata Kupang - Tokan, Alexander Ara Kian; Talok, Damianus; Niha, Simon Sia (LP. Ma'arif Janggan Magetan, 2024)
This research aims to determine the influence of motivation, infrastructure, and the learning environment on students' sports achievements in the Shorinji Kempo sport at SMANKO Flobamorata Kupang. The study employed a quantitative research design with a population consisting of 40 students from grades X, XI, and XII participating in the Shorinji Kempo sport. Data were collected through interviews, questionnaires, and document studies. Descriptive and inferential statistical analyses, including multiple linear regression tests, were utilized to analyze the data, using SPSS version 22. The t-test results indicate that motivation (2.814, sig. 0.039 < 0.05), infrastructure (3.016, sig. 0.008 < 0.05), and the learning environment (3.028, sig. 0.005 < 0.05) have a positive and significant effect on students' sports achievements in Shorinji Kempo. Furthermore, the F-test results show that the three independent variables simultaneously (3.331, sig. 0.030 < 0.05) have a positive and significant impact on students' sports performance. Based on these findings, it is recommended that efforts be made to enhance student motivation and improve the quality of facilities, along with effective management to ensure that students are not overburdened in their learning and training.